Effects of Nucleating Agents on the Properties of Microencapsulated Phase Change Material - Najafi, Hossein; Ghazisaeedi, Reza; Shakeri, Vahid; Shakeri, Amir Reza (Asian Journal of Chemistry, 2010)
The microcapsules containing n-octadecane and nucleating agents with about 1 μm in average diameter were prepared through in situ polymerization. The effects of nucleating agents, i.e. sodium chloride, 1-octadecanol and paraffin, on the crystallization properties, morphology and dispersibility of microcapsules were investigated by using SEM and DSC. The super-cooling was prevented by adding sodium chloride to the emulsion, however, the surfaces of the microcapsules were rough and the microcapsules were worse dispersed. Adding 1-octadecanol in core material was found to prevent microcapsules from super-cooling, but the surfaces of the microcapsules were rough and the microcapsules were easily conglomerated. Microcapsules containing 20 wt % paraffin in core material were free from super-cooling. And paraffin had no influence on the morphology and dispersibility of microcapsules.